Influenza vaccine coverage and the attack rate of influenza-like illness among the elderly in Portugal: is there a correlation? - Nunes, Baltazar (2007)
Vaccination of the elderly (>=65 years of age) against influenza is recommended in all European countries and believed to significantly reduce influenza-related morbidity and mortality [1]. However, there hav e been relatively few studies on the relationship between the vaccine coverage and the attack rate of influenza-like illness (ILI), and their results have differed [2,3,4]. The study described in this paper aimed at establishing the correlation between the influenza vaccine coverage rates and the rates of ILI among Portuguese population aged 65 years and older, during the influenza seasons 1998-1999 to 2006-2007.